Nationalité, internationalisme et visée coloniale dans les mandats français (1920-1946) - Philippe Bourmaud (Revue des Mondes Musulmans et de la Méditerranée)
The drafting and enforcement of nationality laws in post-Ottoman Syria and Lebanon was influenced in various ways by the French Mandate. The formal provisions of the Mandate were of little avail. If anything, the mandate made the legal situation of Mandate citizens abroad more precarious, as they tended to be treated as less than subjects of formal colonies. League of Nations discussions on Mandate nationality laws focused on strengthening the distinction between mandates and Empire territories, rather than giving the status of the inhabitants of the territories under A, B and C Mandate international backing. This and the competitive demographic engineerings of the post-Ottoman nations by the various states of the region weakened Syrian and Lebanese nationalities in comparison with state-sponsored nationalities codified by other post-Ottoman states. Indeed, mandate national status came gradually to be seen by colonial subjects as a fig leaves for demographic experiments under League of Nations cover.